2016
DOI: 10.1590/1807-3107bor-2016.vol30.0018
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of a silicone-based endodontic sealer and two conventional sealers

Abstract: In vitro antibacterial activity of a silicone-based endodontic sealer and two conventional sealers Abstract: The aim of this study was to evaluate whether the modification in the silver component is capable of providing GuttaFlow 2 with antibacterial activity against Enterococcus faecalis compared with epoxy resin-based (AH Plus) and zinc oxide and eugenol-based (Endofill) sealers. The antibacterial activity was evaluated using a reference strain of E. faecalis (ATCC 29212). Freshly mixed sealers were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
2
13
0
3
Order By: Relevance
“…Nevertheless, the current results agree with others that show biocompatibility of GuttaFlow original formulation (17,18). This outcome was expected since GuttaFlow 2 presents basically the same composition, and the modified silver microparticles present a smaller number of atoms in their surface compared to nanoparticles (11,12). A previous investigation had confirmed that these features reduce citotoxicity (25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, the current results agree with others that show biocompatibility of GuttaFlow original formulation (17,18). This outcome was expected since GuttaFlow 2 presents basically the same composition, and the modified silver microparticles present a smaller number of atoms in their surface compared to nanoparticles (11,12). A previous investigation had confirmed that these features reduce citotoxicity (25).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, the sealer formulation was modified and GuttaFlow 2 was introduced. Its composition is basically the same of the original product, but nanosilver particles were replaced by micro-silver particles (11)(12). The evaluation of GuttaFlow new formulation is necessary since the biological effects of silver particles depends on its size and surface that are in contact with tissues (13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Although no study has yet assessed the antibacterial activity of a silver fiber post; similarly to our results, many Authors have reported the antimicrobial effects of AgNPs incorporated in different dental materials. Some researchers have introduced nanosilver-gutta-percha, as an attempt to improve the antibacterial effect of gutta-percha (36). Other studies demonstrated the bactericidal activity of composite resins containing silver nanoparticles and the positive effects of AgNPs on MTA antimicrobial activities (32,37).…”
Section: Discussionmentioning
confidence: 99%
“…Wainsteim et al, en el año 2016, evaluaron la actividad antimicrobiana, frente al Enterococcus faecalis, in vitro, de dos selladores convencionales, entre estos AH Plus determinando la medida del halo inhibitorio de este sellador con un valor de 9,47 mm (14). Los resultados de los estudios de Wainsteim, descritos anteriormente, mostraron halos de inhibición provocados por AH Plus mayores al encontrado por el sellador Topseal, debido a que en dichos estudios se crearon pozos en la superfi cie del agar, de esta manera se obtuvo un contacto directo de los selladores y el microorganismo, mientras que en la presente investigación los selladores estaban contenidos en discos de papel cartulina que se pusieron en contacto con el agar sobre el cual se sembró el Enterococcus faecalis.…”
Section: Efi Cacia Antibacteriana De Tres Selladores Endodónticos Freunclassified
“…El presente estudio demostró la efi cacia antibacteriana del sellador endodóntico a base de óxido de Zinc y Eugenol (Grossfar) cuyo promedio del halo inhibitorio fue de 8,4 mm; resultados similares a esta investigación se encontraron en otros estudios. Wainstein et al, en el año 2016, demostraron la efi cacia antibacteriana del sellador a base de óxido de zinc y eugenol (Endofi ll) frente al Enterococcus faecalis el cual generó un halo inhibitorio de 8,46 mm, similar al halo inhibitorio formado por Grossfar (sellador a base de OZE) de 8,4 mm, utilizado en esta investigación (14).…”
Section: Efi Cacia Antibacteriana De Tres Selladores Endodónticos Freunclassified